Formation Process of Y2O3:Bi3+, Eu3 + Nanosheets from Hydroxide Precursor Nanosheets. (27th September 2021) - Matsunaga, Takuya; Iso, Yoshiki; Isobe, Tetsuhiko
Abstract : We studied the formation of Y2 O3 :Bi 3+, Eu 3+ nanosheets from different Y2 O3 precursors to propose a mechanism for their formation. One limitation of solar cells is their low sensitivity to near-ultraviolet light, which may be improved by including a phosphor to convert near-ultraviolet light to visible light, which can be readily absorbed. An attractive phosphor for this role is Y2 O3 :Bi 3+, Eu 3+ ; however, it remains unclear how Y2 O3 :Bi 3+, Eu 3+ forms from Y2 O3 precursor nanosheets. Therefore, we studied the formation of Y2 O3 :Bi 3+, Eu 3+ nanosheets from Y2 O3 precursors fabricated under various conditions including different pH, base type, and autoclave duration. We found that single-crystalline Y2 O3 :Bi 3+, Eu 3+ nanosheets formed from Y2 O3 precursor nanosheets produced under suitable conditions. The Y2 O3 :Bi 3+, Eu 3+ nanosheets retained the crystallographic orientation of the precursor Y2 O3 nanosheets. The formation of these nanosheets did not require the presence of organic ligands. Our findings indicate that Y2 O3 :Bi 3+, Eu 3+ nanosheet formation involved anisotropic assembly of crystallized nanoparticles and a subsequent dissolution–recrystallization process. The Y2 O3 :Bi 3+, Eu 3+ nanosheets fabricated under certain conditions displayed absorption and emission properties suitable for use as solar converters.